Nonresonant ionization of oxygen molecules by femtosecond pulses: plasma dynamics studied by time-resolved terahertz spectroscopy - Mics, Zoltan; Kadlec, Filip; Kuzel, Petr; Jungwirth, Pavel; Bradforth, Stephen E; Apkarian, V Ara (The Journal of chemical physics, 2005)
We show that optical pump-terahertz probe spectroscopy is a direct experimental tool for exploring laser-induced ionization and plasma formation in gases. Plasma was produced in gaseous oxygen by focused amplified femtosecond pulses. The ionization mechanisms at 400- and 800-nm excitation wavelengths differ significantly being primarily of a multiphoton character in the former case and a strong-field process in the latter case. The generation of the plasma in the focal volume of the laser and its expansion on subnanosecond time scale is directly monitored through its density-dependent susceptibility. A Drude model used to evaluate the plasma densities and electron-scattering rates successfully captures the observations for a wide range of pump intensities. In addition, rotational fingerprints of molecular and ionic species were also observed in the spectra.